Rozwiązane

uzasadnij równość:
a) √2÷2=4do potęgi -0,05÷ 4 do potęgi⅕
b) ³√0,04⁻¹ ÷ 5⁶×0,2⁻²=³√0,2÷√25⁷
c) ²⁹√2do -2,5×4do -⅕ (to wszystko pod pierwiastkiem)=1÷2do -0,1



Odpowiedź :

a) √2÷2=4do potęgi -0,05÷ 4 do potęgi⅕

Lewa strona=√2÷2=2^(1/2):2^1=2^(1/2-1)=2^(-(1/2))=2^(-0,5)

Prawa strona=4^(-0,05):4^(1/5)=4^(-0,05-1/5)=4^(-0,25)=
=(2^2)^(-0,25)=2^(-0,5)

L=P

b) ³√0,04⁻¹ ÷ 5⁶×0,2⁻²=³√0,2÷√25⁷

L=³√0,04⁻¹ ÷ 5⁶×0,2⁻²=(0,04)^(-1/3):5^6*(1/5)^(-2)=(4/100)^(-1/3):5^6*5^2=(1/25)^(-1/3):5^8=25^(1/3):5^8=5^(2/3):5^8=
=5^(2/3-8)=5^(-22/3)

P=³√0,2÷√25⁷=(1/5)^(1/3):5^(14/2)=5^(-1/3):5^7=5^(-22/3)

L=p

c) ten przykład dla mnie jest niejasny, być może zapis jest błędny